2002
DOI: 10.1197/aemj.9.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Contraception Provision: A Survey of Emergency Department Practitioners

Abstract: Abstract. Objectives: To determine emergency department (ED) practitioner willingness to offer emergency contraception (EC) following sexual assault and consensual sex, and to compare responses of practitioners from states whose laws permit the refusal, discussion, counseling, and referral of patients for abortions (often called ''opt-out'' or ''abortion-related conscience clauses'') with those of practitioners from states without these laws. Methods: Using a structured questionnaire, a convenience sample of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…14 A 2002 national survey of all Catholic hospitals in the United States showed that overall, only 5% would provide EC upon request and only 28% would provide EC in cases of rape. 15 In a study by Keshavarz et al, practitioners self-reported that they were less willing to prescribe EC after consensual sex than after sexual assault, 16 which is consistent with the trends in the findings of this study, although in our study they were found not to be statistically significant.…”
Section: Discussionsupporting
confidence: 90%
“…14 A 2002 national survey of all Catholic hospitals in the United States showed that overall, only 5% would provide EC upon request and only 28% would provide EC in cases of rape. 15 In a study by Keshavarz et al, practitioners self-reported that they were less willing to prescribe EC after consensual sex than after sexual assault, 16 which is consistent with the trends in the findings of this study, although in our study they were found not to be statistically significant.…”
Section: Discussionsupporting
confidence: 90%
“…Previous research has shown that hospitals do not consistently provide emergency contraception to victims of sexual assault. [1][2][3][4][5] One study of emergency physicians found 8.4% would not prescribe emergency contraception to sexual assault victims. 1 A 2002 national study of Catholic and non-Catholic hospitals by Harrison found that emergency contraception was not available at 55% of Catholic hospitals and 42% of non-Catholic hospitals.…”
mentioning
confidence: 99%
“…15 The second study, a survey of Pennsylvania emer-gency departments in 2000, found that 32% of non-Catholic and 6% of Catholic hospitals routinely offered counseling and provision of EC to rape patients. 18 The Pennsylvania survey also found that rural emergency departments were less likely to offer EC than were urban emergency departments. 16 In addition, a 2002 national survey of Catholic hospitals found that 28% of Catholic emergency departments offered EC to rape patients (although a majority of these hospitals set up obstacles, such as pregnancy testing and police reports) and 5% offered EC to women who had consensual sexual intercourse.…”
mentioning
confidence: 99%